Premier sondage dans l’abri gravé d’Akirsa (Wolayta, Éthiopie) - Benoît Poisblaud (Afrique Archéologie Arts, 2002)
Preliminary excavation at the base of an/the engraved wall of the Akirsa rockshelter revealed a lithic industry, mainly composed of segments, over a depth of more than 2 meters. Preliminary observation of the material shows a reduction of size over time. The relationship of these occupations to the engravings is still difficult to determine. This 'sanctuary' would seem to have been occupied by groups of hunters over a period time, probably within the last millenia BC.